Identifikasi Jenis Kupu-Kupu di Hutan Kota Muhammad Sabki Jambi untuk Pengembangan Media Pembelajaran Video pada Siswa Kelas X SMA: Identification Butterfly Species in The Forest Muhammad Sabki Jambi for the Development of Video Learning Media in Class X SMA Students - Loly Nadila Putri R.; Asni Johari; Desfaur Natalia (Universitas Jambi, 2021)
Interest in learning is an essential factor that determines the success of learning. The low interest in learning can be overcome by using engaging learning media. This study aims to identify the species of butterflies found in the Muhammad Sabki Forest, Jambi City, to develop video learning media using Wondershare Filmora about the types of butterflies, and to find out the responses of teachers and students of Class X SMA to the learning media. This research was conducted at SMAN 11 Muaro Jambi and in the City Forest of Muhammad Sabki Jambi City. This study used the ADDIE development model (Analysis, design, development, implementation, and evaluation). Types of data obtained in the form of quantitative and qualitative data. Butterflies obtained from the Muhammad Sabki City Forest, Jambi City, consisted of the Nymphalidae and Hesperiidae families. The results of material expert validation were 97.5%, and the results of media expert validation were 96.2% (very good category). The results of the teacher's assessment of biology subjects were 100% (very good category), the small group trial results were 91.7%, and the results of the large group trial were 87.91% (very good category).